Dividend Policy from the Perspective of Ownership and Governance: An Empirical Study in the Construction Sector - Ryo Setyadi; Fitriasuri (LP2M IAIN Palopo, 2026)
This study investigates the determinants of dividend policy from the perspective of ownership structure and corporate governance in the construction sector listed on the Indonesia Stock Exchange during 2018–2023. The research aims to analyze the effects of public ownership, debt policy, asset growth, and the proportion of independent commissioners on dividend policy. Employing a quantitative explanatory approach, the population consists of 29 construction companies, with purposive sampling resulting in 5 companies consistently distributing dividends over six years, yielding 30 observations. Data were collected through documentation of audited financial statements and analyzed using multiple regression with SPSS, including classical assumption tests. The results reveal that debt policy and asset growth have a significant negative effect, while independent commissioners have a significant positive effect on dividend policy. Public ownership does not significantly influence dividend policy. The study concludes that internal factors, especially capital structure and governance, are crucial in shaping dividend policy, while external factors remain a limitation. Future research should expand the sample and include macroeconomic variables for broader generalization